TINJAUAN YURIDIS MENGENAI PUTUSAN HAKIM PENGADILAN TATA USAHA NEGARA NOMOR 31/G/2011/PTUN-PBR BERDASARKAN PERSPEKTIF HUKUM KEUANGAN NEGARA - Kevin Fausta Zahran; Siftiana Sariyatul Arzaqiyah; Revo Handhika Juang (Fakultas Hukum Universitas Djuanda, 2023)
This article will discuss the results of the judge's decision at the State Administrative Court Number 31/G/2011/PTUN-Pbr based on the perspective of state financial law. Administrative Court is a judicial institution that specifically handles legal disputes and relates to Administrative Court between the government and individuals or rechtspersoon. If there is a problem related to state finances, the Administrative Court tries to ensure that the dispute is resolved when a lawsuit is brought to the Administrative Court. The aim of this research is to find out the legal provisions related to the filing of a lawsuit in a state financial case to the Administrative Court and to understand the analysis related to the decision of the PTUN judge No. 31/G/2011/PTUN-Pbr based on the perspective of state financial law. This research is a normative legal research using a case approach and statutory approach. Sources of data were obtained through document and literature studies by collecting data and research sources through articles, journals and various other documents. The results of the study show that the decision Number: 31/G/2011/PTUN-Pbr is a disputed case decision regarding the TUN decision letter, which is also related to state finances.